Crosstalk between G protein-coupled receptors (GPCRs) and tyrosine kinase receptor (TXR) in the heart after morphine withdrawal - Almela, Pilar; Garcia-Carmona, Juan-Antonio; Matínez-Laorden, Elena; Milanés, M Victoria; Laorden, María-Luisa (Frontiers in Pharmacology, 2013)
G protein-coupled receptors (GPCRs) comprise a large family of membrane receptors involved in signal transduction. These receptors are linked to a variety of physiological and biological processes such as regulation of neurotransmission, growth and cell differentiation among others. Some of the effects of GPCRs are known to be mediated by the activation of mitogen-activated extracellular kinase (MAPK) pathways. Cross-talk among various signal pathways plays an important role in activation of intracellular and intranuclear signal transduction cascades. Naloxone-induced morphine withdrawal leads to an up-regulation of adenyl cyclase-mediated signalling, resulting in high expression of protein kinase (PK) A. In addition, there is also an increased expression of extracellular signal regulated kinase (ERK), one member of MAPK. For this reason, the crosstalk between these GPCRs and receptors with tyrosine kinase activity (TKR) can be considered a possible mechanism for adaptive changes that occurs after morphine withdrawal. Morphine withdrawal activates ERK1/2 and phosphorylated tyrosine hydroxylase (TH) at Ser31 in the right and left ventricle. When N-(2-guanidinoethyl)-5-isoquinolinesulfonamide (HA-1004), a PKA inhibitor was infused, the ability of morphine withdrawal to activate ERK, which phosphorylates TH at Ser31, was reduced. The present finding demonstrated that the enhancement of ERK1/2 expression and the phosphorylation state of TH at Ser31 during morphine withdrawal are dependent on PKA and suggest cross-talk between PKA and ERK1/2 transduction pathway mediating morphine withdrawal-induced activation of TH. Increasing understanding of the mechanisms that interconnect the two pathway regulated by GPCRs and TKRs may facilitate the design of new therapeutic strategies.